Para-phenylenediamine, an oxidative hair dye ingredient, increases thymic stromal lymphopoietin and proinflammatory cytokines causing acute dermatitis - Lee, Jae Kwon (Toxicol Res, 2020)
Due to high consumption of cosmetics in modern society, people are always exposed to the risk of skin damage and complications. Para-phenylenediamine (P-PD), an ingredient of hair dye, has been reported to cause allergic contact dermatitis. However, the mechanism has not been well elucidated. Here, we identify that P-PD causes dermatitis by increasing thymic stromal lymphopoietin (TSLP) and inflammatory cytokines. Topical application of P-PD to mouse ear skin in consecutive 5 days resulted in dermatitis symptoms and increased ear thickness. TSLP production in skin was upregulated by P-PD treatment alone. In addition, P-PD-induced TSLP production was potentiated by MC903, which is an in vivo TSLP inducer. P-PD increased TSLP production in keratinocytes (KCMH-1 cells and phorbol 12-myristate 13-acetate-stimulated PAM212 cells). The production of proinflammatory cytokines such as IL-1β, IL-6, IFN-γ, and CCL2, was upregulated by P-PD treatment together with MC903. The results show that repeated exposure to P-PD causes acute contact dermatitis mediated by increasing the expression of TSLP and proinflammatory cytokines.